Therapeutic Effect of Tetramethylphrazine on Cognitive Impairment After Subarachnoid Hemorrhage: An Experimental Study - Zhou, Feng; Fang, Yudan; Zhu, Xiangdong (Asian Journal of Chemistry, 2011)
Tetramethylphrazim is an alkaloid monomer purified from Chinese herb Chuanxiong (rhizome of Ligusticum wallichii). Tetramethylphrazim can improve micro-circulation and increase cerebral blood flow in the ischemic tissue and has been widely used in the treatment of cardio and cerebral ischemic diseases. We tried to evaluate the therapeutic effect of tetramethylphrazim on cognitive impairment after subarachnoid hemorrhage in a rat model. 70 SD rats were randomly divided into control group, subarachnoid hemorrhage group and tetramethylphrazim-treated group. The subarachnoid hemorrhage model was induced by an endovascular filament. The capability of learning and memory was tested by Morris water maze. The level of superoxide dismutase (SOD) in brain tissue was assayed by a xanthine oxidase assay kit with a spectrophotometer. The subarachnoid hemorrhage group exhibited seriously spatial learning and memory impairment in both place navigation trail test and spatial probe trial. In place navigation trail test the mean values of escape latency of tetramethylphrazim-treated group were shorter than those of subarachnoid hemorrhage group (p < 0.05). In spatial probe trial, there were significant differences in the frequency of crossing the former platform site between tetramethylphrazim-treated group and subarachnoid hemorrhage group (p < 0.05). In tetramethylphrazim-treated group, compared with subarachnoid hemorrhage group, the activity of SOD increased significantly (p < 0.05). In conclusion, tetramethylphrazim could improve spatial learning and memory impairment caused by subarachnoid hemorrhage and the raising of activity of SOD in brain tissue may be involved in its mechanism.